Bones : inside and out - Meals, Roy A. (W.W. Norton & Company, 2020)
"A lively, illustrated exploration of the 500-million-year history of bone, a touchstone for understanding vertebrate life and human culture. Bone is ubiquitous and versatile, and uniquely repairs itself without scarring. However, we rarely see bone in its living state-and even then, mostly in two-tone images that only hint at its marvels. After it serves and protects vertebrate lives, bone reveals itself in surprising ways, sometimes hundreds of millions of years later. In Bones, orthopedic surgeon Roy Meals explores and extols this amazing material that both supports and records vertebrate life. He demystifies the biological makeup of bones; how they grow, break, and heal; and how medical innovations-from the first X-rays to advanced surgical techniques-enhance our lives. With enthusiasm and humor, Meals also reveals the enduring presence of bone outside the body-as fossils, ossuaries, tools, musical instruments-and celebrates allusions to bone in history, religion, and idiom. Approachable and entertaining, Bones richly illuminates our bodies' essential framework"--